Thermal wood modification chemistry analysed using van Krevelen's representation. (1st August 2013) - Willems, W; Mai, C; Militz, H
<x xml:space="preserve">Abstract</x> Wood compositional changes during thermal modification follow a characteristic trajectory when mapped in a van Krevelen diagram. The trajectories of widely different wood species appear to merge into a single master curve, suggesting a common thermal modification chemistry shared by these wood species. The largest effect of thermal modification on the chemical composition can be explained by dehydration reactions, followed by decarboxylation reactions. A carbon valence electron donor-acceptor model is proposed, which relates the observed compositional changes to changes in polarity and redox character, which in turn are related to the characteristic hydrophobic and fungal resistance effects on wood by thermal modification.